Shifting social representations of orcas: Content and prototypical analysis - Godinho, S.; Garrido, M. V. (Environmental Communication, 2025)
Conservation advocates researching the mediatization of human-wildlife relations suggest that negatively charged discourses may jeopardize conservation efforts. Following recent reports of orcas harassing and even ramming yachts in the Portuguese and Spanish coastlines, the present research examines how orcas are described in online media, how the general public perceives them, and how the current situation is shaping their social representations. Across two studies, we scrutinize online reporting and stereotypical representations of orcas held by people aware (vs. naïve) of the situation. Study 1 indicates that following the onset of this new behavioral pattern, online information about wild orcas increased significantly and became more negative and abstract. Study 2 shows that conflict-related evocations are absent from the core of orcas’ social representations but appear in peripheric dimensions, with aware participants describing orcas with conflict-related words (e.g., attack) to convey their perception of these animals as perpetrators. The current situation antagonizing humans to orcas is far from being understood, let alone solved. Since social representations shape social behavior, influencing how humans act, interpret, and anticipate interactions with other species, understanding how orcas are portrayed supports interspecies relations and human-wildlife conflict research, while informing future conflict mitigation strategies.